The public investment projects and their relationship with the development of tourism activity - Garcia-Ponce, Sara H. (2023)
The purpose of the study was to evaluate the impact of public investment projects (PIP) on the development of tourism activities in the province of Huánuco. The study was developed under a quantitative approach, it was basic in nature, with deductive method, non-experimental design and cross section. The sample was made up of 34 PIPs developed in the province of Huánuco. The technique used was observation and the instruments were record sheets and electronic references. The inferential analysis was performed using Pearson's Chi-square test, whose p-value obtained was 0.000<0.005. This means that the PIPs executed by the central government in the local governments of the province of Huánuco during 2015 have a significant relationship with the progress of tourism activity. Of the total number of projects evaluated according to their degree of impact on the development of tourism, it was found that they range from a medium to high level. Regarding the projects developed by local governments, it was found that their degree of influence on the development of tourism ranges between medium and high. It is concluded that PIPs have a significant effect on the growth of tourism activities.